Influence of Interlocking Horizontal Mattress Epitendinous Suture Placement on Tendinous Biomechanical Properties in a Canine Common Calcaneal Laceration Model - Cocca, Christina J.; Duffy, Daniel J.; Kersh, Mariana E.; Moore, George E. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective This article evaluates the effect of an interlocking horizontal mattress epitendinous suture (IHMES) in addition to a three-loop pulley (3LP) core suture for canine tendon repair.Study Design Twenty-eight cadaveric common calcaneal tendons were randomized, sharply transected and repaired with either a 3LP or 3LP + IHMES. Tensile loads required to create a 1- and 3-mm gap, yield, peak and failure loads, and mode of failure were analysed. Significance was set at p < 0.05.Results Mean ± standard deviation yield and failure force for 3LP + IHMES was 178.0 ± 45.3 N and 242.1 ± 47.8 N, respectively, which was significantly greater compared with 3LP alone, 97.9 ± 36.2 N and 119.3 ± 35.6 N (p < 0.0001). Occurrence of 3-mm gap formation was significantly less in the 3LP + IHMES group (p < 0.013). Mode of failure was significantly different between the groups (p < 0.001) with 3LP + IMHES patterns failing by suture breakage (13/14) compared with suture pull-through in the 3LP (11/14).Conclusion Addition of an epitendinous suture pattern significantly reduced gap formation between tendon ends and significantly increased loads at yield (1.8 × ), peak (2.0 × ) and failure (2.0 × ) force of repairs. Use of an epitendinous suture should be considered to significantly increase biomechanical strength of repairs; however, further in vivo testing is necessary to evaluate its effect on tendinous blood supply.
Keywords: dog; tendon; epitendinous; tenorrhaphy; interlocking horizontal mattress